Outcomes of annual surveillance imaging in an adult and paediatric cohort of succinate dehydrogenase B mutation carriers. (24th October 2016) - Tufton, Nicola; Shapiro, Lucy; Srirangalingam, Umasuthan; Richards, Polly; Sahdev, Anju; Kumar, Ajith V.; McAndrew, Lorraine; Martin, Lee; Berney, Daniel; Monson, John; Chew, Shern L.; Waterhouse, Mona; et al.
Summary: Objective: For 'asymptomatic carriers' of the succinate dehydrogenase subunit B ( SDHB ) gene mutations, there is currently no consensus as to the appropriate modality or frequency of surveillance imaging. We present the results of a surveillance programme of SDHB mutation carriers. Design: Review of clinical outcomes of a surveillance regimen in patients identified to have an SDHB gene mutation, based on annual MRI, in a single UK tertiary referral centre. Patients: A total of 92 patients were identified with an SDHB gene mutation. a total of 27 index patients presented with symptoms, and 65 patients were identified as asymptomatic carriers. Measurements: Annual MRI of the abdomen, with alternate year MRI of the neck, thorax and pelvis. Presence of an SDHB‐ related tumour included paraganglioma (PGL), phaeochromocytoma (PCC), renal cell carcinoma (RCC) and gastrointestinal stromal tumour (GIST). Results: A total of 43 PGLs, eight PCCs and one RCC occurred in the 27 index patients (23 solitary, four synchronous, five metachronous). A further 15 SDHB‐ related tumours (11 PGLs, three RCCs, one GIST) were identified in the asymptomatic carriers on surveillance screening (25% of screened carriers): 10 on the first surveillance imaging and five on subsequent imaging 2–6 years later. A total of 11 patients had malignant disease. Conclusions: SDHB‐ related tumours are picked up as early as 2 years after initial negative surveillance scan. We believe the high malignancy rate and early identification rate of tumours justifies the use of 1–2 yearly imaging protocols and MRI‐based imaging could form the mainstay of surveillance in this patient group thereby minimizing radiation exposure.